Variation of innovation: a review of income maintenance programmes available to the self-employed in nine European countries during the 2020 Covid-19 pandemic - Clarkson, M (2021)
The pandemic and resulting deteriorating business and macroeconomic situation reinforced existing divisions as atypical workers like the self-employed experienced higher levels of shock exposure (Avlijaš, 2020; OECD, 2020a). The income maintenance schemes made available to the self-employed in response marked a historic moment of welfare state expansion, but provision varied widely. A Fuzzy-set Ideal Type Analysis of provision in Austria, Denmark, Finland, Italy, Greece, the Netherlands, Poland, Romania and the UK reveals empirical support for three theoretical models of income maintenance schemes though model memberships differ to the Three Worlds of Welfare Capitalism typology. The findings highlight the unique nature of the emergency provision but also of the self-employed and reinforces a need for more theoretical focus on this growing group of diverse, and often precarious, workers. Barriers to accessing these schemes underscores the need for more flexible social protection systems to accommodate non-standard forms of labour. This is an imperative if self-employment continues to increase as countries promote flexible labour markets as part of an economic recovery strategy.